The development of learning models using social media based on building theory Self-knowledge The Big Sik concept and examination group learning process in information field. 21st century media and technology for middle school students - พิชญ์ประเสริฐ, ปิยะพันธ์ (Research and Development Journal Sisaket Rajabhat University, 2020)
The purposes of this research were 1) to study the effects of using learning model from Social Media in Constructionism, The Big Six Skills Model and Group Investigation Model for information, media and technology in 21st Century for Secondary School Students, and 2) to study the students’satisfaction toward learning model from Social Media in Constructionism, The Big Six Skills Model and Group Investigation Model for information, media and technology in 21st Century for Secondary School Students. The samples were mathayomsuksa 3 students which divided into experimental group and control group in Photatprachason school, obtained by cluster random sampling. The instruments were learning course using this model, achievement test, information media and technology test, and satisfaction questionnaire. The data were analyzed by mean, standard deviation, t-test. The research revealed; 1) The effectives of this developed model found that (1.1) the mean of experimental group’s information media and technology test was significantly higher than the control group at the level of .05 (1.2) the mean of experimental group’s learning achievement after learning was significantly higher than the control group at the level of .05 2) As a whole, the students’ satisfaction toward learning model using Social Media was at the high leve